Effect of daily alcohol intake on sex hormone levels among postmenopausal breast cancer survivors on aromatase inhibitor therapy: a randomized controlled crossover pilot study - Elizabeth Mostofsky; Julie E. Buring; Steven E. Come; Nadine M. Tung; Cancan Zhang; Kenneth J. Mukamal (Breast Cancer Research, 2025)
Abstract Background Alcohol intake is associated with a higher risk of estrogen receptor-positive (ER+) breast cancer (BC), presumably through its confirmed ability to increase sex hormone levels. Whether consuming alcohol within the recommended limit of one serving per day increases sex hormone levels among postmenopausal women taking aromatase inhibitors (AI) to inhibit estrogen production remains unknown. Therefore, we compared sex hormone levels following white wine to levels following white grape juice among ER + BC survivors taking AIs. Methods In this 10-week randomized controlled two-period crossover trial conducted from September 2022 to July 2023 among 20 postmenopausal women on AIs, we examined within-person changes in sex hormone levels following 3 weeks of 5 ounces of white wine daily versus 3 weeks of 6 ounces of white grape juice daily, with each drinking period preceded by two-week washouts and drinking period sequence allocated by randomization. Results All 20 participants completed the trial. Compared to daily grape juice, daily wine led to decreases in total estradiol (11.1%, 95%confidence interval[CI] -49.8%,57.2%), free estradiol index (0.7%, 95%CI -2%,0.7%), and free estradiol concentration (7.7%, 95%CI -48%, 63.9%) but increases in estrone (13.8%, 95%CI -9.5%,43.1%), dehydroepiandrosterone sulfate (DHEAS; 11.4%, 95%CI -3.3%,28.4%), and testosterone (12.6%, 95%CI -0.8%,27.7%) and decreased sex hormone-binding globulin (SHBG; -2.7%, 95%CI -21.9%,21.2%). Conclusions Five ounces of white wine daily did not lead to statistically significant increases in estradiol, but it led to changes in other sex hormones suggesting higher BC risk. Whether this level of alcohol intake diminishes AI effectiveness warrants further investigation. Trials Registration Clinicaltrials.gov NCT05423730 registered June 14, 2022.